Christy [videorecording (Blu-Ray)] - Partos, Antony (Black Bear Pictures, 2026)
"Christy Martin never imagined life beyond her small-town roots in West Virginia--until she discovered a talent for knocking people out. Her toughest battles unfold outside the ring, involving family, identity, and Jim, her trainer and manager-turned-husband. Based on remarkable true events, Christy Martin's story is one of resilience, courage, and the fight to reclaim one's life."--